1998
DOI: 10.1080/00034989859285
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of acute adenolymphangitis in brugian filariasis: comparison of the efficacy of ivermectin and diethylcarbamazine, each combined with local treatment of the affected limb

Abstract: Acute attacks of adenolymphangitis (ADL) not only force patients with lymphatic filariasis to seek medical attention but also hasten the progression of filarial oedema. Patients with filariasis-associated ADL are currently treated with repeated courses of the antifilarial drug diethylcarbamazine (DEC), with or without antibiotics and anti-inflammatory agents. In this double-blind, placebo-controlled study, the efficacy of local treatment of the affected limb combined with repeated doses of ivermectin or DEC, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 10 publications
4
14
0
Order By: Relevance
“…The rate of ADLA was lowest six months after enrollment, yet a decrease was sustained over the two year period of the study. These findings are consistent with other studies which have also found a decrease in ADLA episodes following enrollment in a lymphedema management program [2], [3], [13], [14], [23], [24]. Other programs have found a similar plateauing of the ADLA rate 3–12 months after beginning lymphedema management [13], [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The rate of ADLA was lowest six months after enrollment, yet a decrease was sustained over the two year period of the study. These findings are consistent with other studies which have also found a decrease in ADLA episodes following enrollment in a lymphedema management program [2], [3], [13], [14], [23], [24]. Other programs have found a similar plateauing of the ADLA rate 3–12 months after beginning lymphedema management [13], [14].…”
Section: Discussionsupporting
confidence: 91%
“…An ADLA episode was defined by patient self-report of two or more of the following symptoms: redness, pain, or swelling of the leg or foot, with or without the presence of fever or chills, [3], [19]. Patients were asked how many times they had an ADLA episode in the previous 30 days.…”
Section: Methodsmentioning
confidence: 99%
“…On contrary, others reported that the antifilarial drugs (ivermectin and albendazole) even though important in the sustained reduction of blood microfilaria levels, have no role in the management of lymphedema or acute attacks. [26] Epidemiologic associations between transmission intensity and the prevalence of lymphedema have suggested to some investigators that third-stage larvae trigger lymphedema. [2728] This hypothesis is supported by observations of decreases in lymphedema prevalence and severity following mass treatment with antifilarial drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphedema severity was established based on the seven stage classification system developed by Dreyer, et al [16]. ADL episodes were defined as any period of pain, redness, and/or swelling of the affected leg, which may have been accompanied by fever and/or chills [18, 19]. …”
Section: Methodsmentioning
confidence: 99%